SEPARATION AND ELEMENTATION OF DIMER STILBENOID STRUCTURE OF VATICA LIGHT STEEL UMBONATA BURCK (DIPTEROCARPACEAE) - Atun, Sri (Jurnal Penelitian Saintek, 2007)
Three oligostilbenoid, namely (-)-ampelopsin F (1), laevifonol (2), and e-viniferin (3) had been isolated and elucidated these structure from the stem bark of Vatica umbonata Burck (Dipterocarpaceae). The structure of three compounds were elucidated based on physical and spectroscopic data UV,JR, IH and HCNMR, HMBC, HMQC, COSY, andNOESY.